SUSTAINABLE REGENERATION OF MORDENITE MINERAL AS ION EXCHANGER FOR REMOVAL IRON AND MANGANESE IN GROUNDWATER - Septiyani, Elda; Zevi, Yuniati; Arifianingsih, Nur Novilina (MATTER: International Journal of Science and Technology, 2020)
Access to clean water is a basic need for humans. At present, groundwater quality is a fundamental consideration factor in its utilization. Metal removal in groundwater with filtering techniques has been done quite a lot with various media, one of which is zeolite. However, the pore blockage often becomes a problem, so it inhibits the process and shortens the life of the stone in adsorbing iron and manganese, to overcome this problem regeneration is needed so that Mordenite can be reused. This research aims to study the method of regeneration chemically and biologically so as to improve the ability of Mordenite in removing iron and manganese by using a continuous bed reactor with an up-flow system for 60 minutes. Activation and regeneration of Mordenite from natural zeolite is carried out chemically using NH4Cl by immersion method, while biological regeneration is carried out by utilizes Thiobacillus ferrooxidans bacteria. The removal efficiency obtained will decrease as the adsorbent is used. Efforts to increase the adsorption capacity will continue to be carried out by giving chemical and biological regeneration. Furthermore, adsorption capacity and removal efficiency in each variation of Mordenite mineral adsorbents are included in the scope of the research.